Kepastian Hukum Pengaturan Publisitas Pada Program Pendaftaran Tanah Sistematis Lengkap (PTSL) - Restu Adi Putra; Dominikus Rato; Dyah Ochtorina Susanti (Jurnal Ilmu Kenotariatan, 2021)
The Publicity Principle in the Complete Systematic Land Registration Program is the principle that provides juridical data about who is the subject of their rights, what are the names of their rights, and how are their transitions and encumbrances taking place. The principle of publicity in PTSL regulated by article 24 paragraph (2) Permen. ATR/Ka. BPN Nuumber 6 Tahun 2018 governs announcement of physical data and juridical data is foor 14 working days. This is different from the time provisions for the announcement of physical data and juridical data governed by article 26 paragraph (1) PP. Number 24 tahun 1997 regulating the period off announcement of physical and juridical data is 30 working days. The formulation of the problem in this thesis paper consists of three problem formulations.First, is the Publicity Principle in the Complete Systematic Land Registration Program in accordance with the Principle of Legal Certainly at Land Registration in Indonesia, second How the legal remedies of the Certificate from the Registraton Program Compelete Systematic Land, third What are future arrangements for the Systematic Complete Land Registration Program to ensure legal certainly of land rights in Indonesia. The methodology used in writing this thessis is the statute approach, the conceptual approach, and the historical approach. The Publicity Principle of the PTSL program which is regulated differently from PP Number 24 of 1997 provides space for legal uncertainly in the community. This is because the community as seekers of guarantee of land rights can be disadvantaged by reducing the time for submitting anobjection in the PTSL program for 14 working days which PP Number 24 of 1997 is set for30 days. If it is examined with the basic legal principle, namely the principle of lex superior derogat lex inferior, there is also a clear devitation from this principle. Legal uncertainly on the principle of publicity is even clearer if it is reviewed based on the principles of legal certainly that must be contained for a certain rule. There are some elements which cannot be fullfilled by Permen ATR/Ka. BPN Number 8 of 2018 so that in daily practice in society still problems can be found in this publicity principle. The conclusion of this paper is first, the principle of publicity of the PTSL program does not meet the principle of legal certainly. Second, there are two legal actions that can be dealt with by the public if they have objections due to the issuance of the PTSL certifivcate. Third, the Goverment needs to synchronize/ harmonize Permen ATR/Ka. BPN number 6 of 2018 in order to guarantee legal certainly to holders of land rights.